2014
DOI: 10.1002/lt.23874
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and management of hepatic artery thrombosis after adult liver transplantation

Abstract: Hepatic artery thrombosis (HAT) represents a major cause of graft loss and mortality after liver transplantation. It occurs in up to 9% of adult recipients. The early diagnosis of HAT decreases septic complications, multiorgan failure, and graft loss, and there are better outcomes after treatment. In this study, we reviewed 102 episodes of HAT, which were classified as early hepatic artery thrombosis (E-HAT) when they were diagnosed within the first 21 days after transplantation. The overall incidence of HAT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(143 citation statements)
references
References 23 publications
7
132
1
3
Order By: Relevance
“…We observed that high MELD score, CTP C, or severe patients with major complications and mortality were associated with HAT as a risk factor for early death, as reported in the literature [2,17,18].…”
Section: Discussionsupporting
confidence: 58%
“…We observed that high MELD score, CTP C, or severe patients with major complications and mortality were associated with HAT as a risk factor for early death, as reported in the literature [2,17,18].…”
Section: Discussionsupporting
confidence: 58%
“…data]. Furthermore, rearterialized rat OLT models better approximate the physiologic situation and the clinical scenario, where hepatic arterial thrombosis is one of the most dreadful complications and a major cause of graft loss and mortality [99,100]. …”
Section: Technical Issues Concerning P-olt In Ratsmentioning
confidence: 99%
“…Indeed, recent studies have suggested that late HA thrombosis may have a lesser effect on liver function and graft survival and that its incidence may even be underes timated, mainly owing to arterial collateralization allowing adequate hepatic perfusion, although the incidence of a biliary complication remains high in that context. 21 In conclusion, RAR using CIAA represents an effective, safe, and readily available approach for the treatment of HACs in LT patients, with a limited risk of infection. Despite the high rate of HA thrombosis encountered, this strategy provides satisfactory longterm graft and patient survival and should therefore challenge the classical modalities of rescue treatment.…”
Section: Discussionmentioning
confidence: 87%